Egg Quality, Fertility and Hatchability of Laying Quails Fed Diets Supplemented with Organic Zinc, Chromium Yeast or Mannan Oligosaccharides - El-Samee , Laila D. Abd; El-Wardany, I.; Ali, Nematallah G.; Abo-El-Azab, O.M. (International Journal of Poultry Science, 2012)
The aim of this study was to investigate the effect of supplementing diets of laying Japanese quails (n = 250; 8 wk of age) with bioplex zinc, chromium yeast or Mannan Oligosaccharides (MOS) on egg weight, egg quality, fertility, hatchability and hatching chick weight. Diets were a basal diet or the basal diet supplemented with 20 mg bioplex zinc (Zn1), 40 mg bioplex zinc (Zn2), 600 mg Cr yeast (Cr1), 1200 mg Cr yeast (Cr2), 1.0 g MOS, Zn1 plus MOS, Zn2 plus MOS, Cr1 plus MOS or Cr2 plus MOS. Egg weight tended to be higher (p = 0.188) with the tested supplements compared to the control. Egg quality was not affected by the studied supplements. The high zinc diet or Cr2+MOS diet tended to improve egg fertility, while Zn1, Zn1+MOS or Zn2+MOS diets improved egg hatchability (p